Modernizing waqf performance evaluation by waqf management efficiency index / Jaafar Pyeman, Hazriah Hasan and Ismail Ahmad. - Pyeman, Jaafar (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2016)
A strong Waqf system will not only complete the equality for a comprehensive Islamic financial system that supports a more equitable distribution of wealth to ensure justice, it will also use Islamic financial services, particularly in the management and investment of the Waqf funds. Waqf assets in Malaysia are set under the legislation of the religious authority in each state. The diversity of Waqf assets resulted to the disuniformity of Waqf administration and management, and a huge gap existed in the collection and distribution of Waqf funds. This paper aims to measure the efficiency scores of Waqf departments in all states that run Waqf funds in their State Islamic Religion Councils (SIRCs). Data envelopment analysis (DEA) can best measure the Waqf management efficiency (WME) index measurement. In assessing the technical efficiency score of each state, WME index using DEA analysis was applied with the consecutive periods of years of the whole state precisely. The findings showed that the most improving Waqf department of SIRCs is Penang state, which has seen increasing WME Index in four periods of investigation; therefore, this state became the benchmark for the rest of the states in Malaysia.